Capital efficiency and organizational performance: A dynamic panel analysis of Weighted Average Cost of Capital (WACC) and ROA in Indonesia’s healthcare sector - Arofah, Ulfa; Hakim, Muhammad Saiful; Alfarizi, Muhammad (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The healthcare sector in Indonesia faces challenges in managing capital efficiency and organizational performance due to high operational costs and the need for continuous investment in health technology and infrastructure. As a key driver of economic growth, especially post-COVID-19, optimal capital management is crucial for sustaining operations and creating stakeholder value. This study examines the relationship between the Weighted Average Cost of Capital (WACC) and Return on Assets (ROA) in Indonesia’s healthcare sector using a quantitative dynamic panel analysis approach. Financial data from healthcare companies listed on the Indonesia Stock Exchange were analyzed using the Generalized Method of Moments (GMM). The findings indicate that WACC negatively affects ROA, but the relationship is not statistically significant. Leverage, measured through the Debt to Asset Ratio and Debt to Equity Ratio, strengthens this relationship positively. Meanwhile, cash holdings and firm size have a negative moderating effect, whereas Net Working Capital (NWC) reinforces the relationship positively. These results highlight the importance of effective debt and liquidity management in optimizing profitability in the healthcare sector. The study contributes theoretically to capital efficiency discussions and offers practical insights for industry stakeholders, including decision-makers and investors. The research is novel in its focus on Indonesia’s healthcare sector, making it highly relevant for financial and strategic planning in the industry.